Penyuluhan Kontrasepsi Metode Amenorea Laktasi (MAL) Guna Meningkatkan Pengetahuan Ibu Nifas - Andriyani, Dian Tuti; Febrina, Hilda; Halimah, Nur; Latifah, Nurul; Saprina, Okta; Renika, Renika; Utami, Iis Tri (Kreativasi : Journal of Community Empowerment, 2024)
The population density in Indonesia is increasing rapidly, with many breastfeeding mothers delaying the use of contraception due to concerns about interfering with the breastfeeding process for their infants. Contraception is commonly used by mothers after giving birth to space future births; there are many contraceptive options available depending on a mother's knowledge and beliefs in selecting a method. Exclusive breastfeeding serves as a reasonably effective temporary contraceptive method as long as the mother has not menstruated and the infant is less than six months old. The effectiveness of the Lactational Amenorrhea Method reaches 98% for mothers exclusively breastfeeding. The purpose of this outreach is to provide information about the Lactational Amenorrhea Method (LAM). The methods used in this community outreach begin with introductions of the speakers, followed by education on health information, a question and answer session with participants, and closing remarks. This program aims to enable postpartum breastfeeding mothers to utilize LAM as a contraceptive method. The intended outputs of this activity include: Scientific publications in journals with ISSN numbers/Proceedings, video recordings of the activity, improved knowledge and skills of postpartum mothers, and improved community health).